Identification and Characteristics of Marine Debris on the Poka Beach Coast, Ambon Bay: A Quantitative Analysis of Material Composition - Laole Laole; Aniesa Nabila; Kamal Mewar; Salim Souwakil (JUSTE (Journal of Science and Technology), 2025)
Marine debris constitutes an anthropogenic pollutant, causing significant negative impacts on the structure and function of aquatic ecosystems. This research aimed to analyse the composition, spatial distribution, and quantitative characteristics of marine debris along Poka Beach, Inner Ambon Bay. Data collection was conducted in July 2025 using a 100-meter transect method divided into five observation plots measuring 5×5 meters each. Macro marine debris samples (2.5 cm– 1 meter) were identified, classified by material type, and analysed quantitatively for composition, density, and biomass. Results revealed 581 marine debris items with a total biomass of 7,098.62 grams, unevenly distributed across sampling locations. Plastic dominated the composition with 357 items (61.4%) and biomass of 3,382.56 grams (47.7%), followed by plastic foam with 185 items (31.8%) and biomass of 219.03 grams (3.1%). Debris density varied significantly between 1.8–8.8 items/m², averaging 4.64 ± 2.87 items/m². Plot 2 showed the highest accumulation (220 items, 8.8 items/m²), while Plot 4 showed the lowest (45 items, 1.8 items/m²). High-density materials such as wood (1.5% of items) and rubber (2.2% of items) contributed significantly to biomass at 26.2% and 15.2%, respectively. Spatial distribution heterogeneity (CV=61.9%) indicates the influence of local hydrodynamic factors and proximity to anthropogenic pollutant sources. Plastic dominance is consistent with global patterns; however, high spatial variability demonstrates the importance of adaptive management approaches. This research provides baseline data for developing marine debris pollution mitigation strategies in Eastern Indonesia and supports sustainable management program implementation.